Epidemiology of the Zika virus outbreak in the Cabo Verde Islands, West Africa - Lourenço, J; de Lourdes Monteiro, M; Valdez, Y; Monteiro Rodrigues, J; Pybus, O; Rodrigues Faria, N (Public Library of Science, 2018)
Introduction: The Zika virus (ZIKV) outbreak in the island nation of Cabo Verde was of unprecedented magnitude in Africa and the first to be associated with microcephaly in the continent.